Dam Construction Impacts on Flow Stability: Evidence of a Hydrological Regime Shift in the Bulango Watershed, Gorontalo - Djuraini, Moh. Fahry (Fakultas Teknik, Universitas Brawijaya, 2026)
Dam construction is known to alter downstream hydrology, yet the early construction phase remains understudied, particularly in tropical monsoon basins where short hydrological records limit attribution. This study quantifies the initial hydrological response of the Bulango River, Gorontalo, during the onset of Bulango Ulu Dam construction (2019) using daily and monthly discharge data from 2014–2024. A combined analysis employing the Modified Mann–Kendall trend test, Pettitt change-point detection, and 33 Indicators of Hydrologic Alteration (IHA) was used to distinguish gradual climatic tendencies from abrupt construction-driven disturbances. After correcting for serial correlation, no significant long-term trend was detected, indicating that the apparent decline in discharge reflects natural hydrological persistence rather than climate-driven change. In contrast, the Pettitt test revealed a statistically robust regime shift in March 2019, coinciding with major river-diversion and excavation activities. IHA results show that although seasonal timing remains largely intact, short-duration hydrologic components have become notably unstable, with significant increases in low-pulse frequency and flow reversals. Overall, the river exhibits a 72.4% degree of hydrological alteration, indicating high-level disturbance during the construction phase. These findings provide one of the first empirical demonstrations that dam construction can induce measurable hydrological alteration well before impoundment, underscoring the need for early-phase monitoring and adaptive construction practices to reduce downstream ecological risks. The pre-impoundment baseline established here serves as a critical reference for evaluating future operational impacts once the reservoir becomes fully functional.